Asymmetries in the Impact of Investor Sentiment on Equity Returns: An Analysis of the Indian Equity Market - George, Saji; Srinivasa Suresh, P. (Indian Journal of Research in Capital Markets, 2015)
This study, on the basis of arguments from behavioural finance literature, examined the nature of impact of investor sentiment on the returns of equity portfolios based on market capitalization. The research was carried out on the four major indices of the Bombay Stock Exchange such as : BSE Sensex, BSE 500, BSE Mid-cap, BSE Small-cap Indices over a period from April 2007 to January 2015. We found evidence of significant positive impact of past level of investor sentiment in determining the current market returns. The impact of sentiment was found to be asymmetric across stock returns of different portfolios and the magnitude of the impact of the sentiment index was found to be higher upon BSE Small-cap and BSE Mid-cap returns as compared to BSE Sensex and BSE 500. The impulse response analysis identified higher levels of positive responses in market returns up to four months into the future to a Cholesky one standard deviation shock in sentiment in the initial period, and the impact of this shock was found to be active at a decreasing rate even after 10 months in the future, confirming the delayed price adjustment processes and excess profit making opportunities in the Indian market. This primary level analysis and the findings leave certain research questions open for further in-depth investigation, specifically : theÂ structural and policy level deficiencies which constrain faster market correction process; the implications of market sentiment upon the momentum formation in the market; the nature of investors and intermediaries ; and trading in medium and small cap securities in the Indian equity market.